Cognition in Emotion : an Investigation through Experiences with Art. - Tone, Roald (Consciousness, Literature and the Arts, 10., 2007)
Emotions are essential for human existence, both lighting the way toward the brightest of achievements and setting the course into the darkness of suffering. Not surprisingly, then, emotion research is currently one of the hottest topics in the field of psychology. Yet to divine the nature of emotion is a complex and extensive task. In this book emotions are approached thought an exploration of the nature of cognition in emotion; the nature of thoughts in feelings. Different approaches to emotions are explored, from brain research to research at the level of experience, and it is argued that a.